Azacytidine-induced hypomethylation delays senescence and coloration in harvested strawberries by stimulating antioxidant enzymes and modulating abscisate metabolism to minimize anthocyanin overproduction. (1st May 2023) - Chen, Yanpei; Li, Dong; Zhang, Xiaochen; Ma, Quan; Xu, Yanqun; Luo, Zisheng
Highlights: AZ shaped hypomethylation with the reprogramming of bio-vitality of strawberries. The resultant changes were involved with the decay, softening, and soluble solids. AZ markedly delayed the coloration and senescence in harvested strawberries. AZ-induced hypomethylation minimized anthocyanin production with the decreased ABA. AZ-induced hypomethylation repressed the ROS level and POD, CAT activities. Abstract: DNA methylation is increasingly known to be essential for fruit ripening and senescence. Currently, 5-azacytidine (AZ) was selected as an effective demethylator and it successfully shaped the genomic hypomethylation in harvested strawberries. This was associated with the reprogramming of global gene expressions, which influenced downstream food traits. The alleviation of decay and softening, as well as the deceleration of soluble solid accumulation, were included. Coloration was also delayed as a result of the AZ-induced hypomethylation. Our examinations of anthocyanin biosynthesis and transport revealed that they were markedly minimized, which was probably involved with the decreased abscisate level and its weakened metabolism. Additionally, under AZ, the retarded postharvest senescence process was observed and it might be induced by the inhibited ROS accumulation accompanying the peroxidase and catalase activities alteration. Overall, these findings underlined the importance of methylation in strawberries and suggested the potential role of epigenetic regulators in the postharvest industry.